Can strained hydrocarbons be “forced” to be stable? - Neudecker, Tim; Günther, Benjamin; Dreuw, Andreas (The journal of physical chemistry. A, Molecules, clusters, and aerosols, 2016)
Many strained hydrocarbons are prone to isomerization, dimerization, and trimerization under normal laboratory conditions. Here we investigate a method to stabilize angle-strained cycloalkynes by applying a mechanical pulling force to the carbon atoms adjacent to the triple bond, which partially linearizes the C≡C-C bond angles. We discuss various methods of applying such pulling forces, including photoswitches and incorporation into additional strained macrocycles. We use the computational JEDI (Judgement of Energy DIstribution) analysis to quantify the distribution of energy in strained cycloheptyne and judge the change in stability upon application of an external force via isodesmic and homodesmotic reactions. We find that cycloheptyne can indeed be stabilized by external forces. However, the force generated by photoswitches during isomerization is too low to lead to a significant stabilization of the molecule. Hence, stronger forces are needed, which can be achieved by incorporating cycloheptyne into a second strained macrocycle.